Beneficial effects of spermidine on cardiovascular health and longevity suggest a cell type-specific import of polyamines by cardiomyocytes. (21st December 2018) - Nilsson, Bengt-Olof; Persson, Lo
Abstract : Recent and exciting in vivo studies show that supplementation with the polyamine spermidine (Spd) is cardioprotective and prolongs lifespan in both mice and humans. The mechanisms behind Spd-induced cardioprotection are supposed to involve Spd-evoked stimulation of autophagy, mitophagy and mitochondrial respiration and improved the mechano-elastical function of cardiomyocytes. Although cellular uptake of Spd was not characterized, these results suggest that Spd is imported by the cardiomyocytes and acts intracellularly. In the light of these new and thrilling data, we discuss in the present review cellular polyamine import with a special focus on mechanisms that may be relevant for Spd uptake by electrically excitable cells such as cardiomyocytes.